Analysis of simulation-based (FEA) strength and durability test modeling of natural fiber reinforced composite materials - Rangga Pratama, Rangga Pratama; Boy Rollastin, Boy Rollastin; Yuliyanto, Yuliyanto (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2026)
The need for lightweight, strong, and environmentally friendly materials in the maritime industry has driven research into natural fiber-based composites as an alternative to metal. Composite materials reinforced with coconut fiber, banana stem, and palm fiber were chosen because of their abundant availability and potential mechanical characteristics for structural applications such as boat bodies. This study aims to model and analyze the flexural strength and impact resistance of composites reinforced with three types of natural fibers using a Finite Element Analysis (FEA) simulation method in ANSYS software. The test standards used include ASTM D790 for three-point flexural tests and ASTM D256 for Izod impact tests. Simulations were carried out with variations in fiber volume fractions of 3%, 5%, and 7% to obtain maximum stress, strain, and deformation responses. The results showed that the banana stem fiber composite had the highest flexural strength of 148.09 MPa, while the palm fiber fiber showed the highest impact resistance of 145.26 MPa. Validation against literature data shows a difference in simulation results of only around ±5%, confirming the accuracy of the numerical model in predicting the mechanical behavior of the composite. The conclusions of this study indicate that the FEA-based simulation approach is effective in assessing the performance of natural fiber composites and confirms their potential use as an alternative material to metals for lightweight structural applications in the maritime sector.